Implementing the Talking Stick Learning Method to Enhance Learning Motivation among Eighth-Grade Students in Islamic Religious Education - Triandini R., Afifah; Raupu, Sumardin; Amin, Muh. Agil (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study examines the implementation of the Talking Stick learning method to enhance students’ learning motivation in Islamic Religious Education among eighth-grade students. The research was motivated by low student participation, limited classroom interaction, and the dominance of teacher-centered instruction, which reduced students’ engagement and enthusiasm during learning activities. Therefore, the study aimed to analyze the effectiveness of the Talking Stick learning method in improving students’ learning motivation and classroom participation. This study employed a quantitative approach using Classroom Action Research based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages conducted over two cycles. The participants were 17 eighth-grade students selected purposively based on preliminary observations indicating low learning motivation. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive quantitative techniques. The findings revealed that the Talking Stick learning method significantly improved teacher instructional performance, student participation, and learning motivation. Teacher activity increased from 76.78% in Cycle I to 98.21% in Cycle II, while student participation improved from 64.28% to 91.07%. In addition, students’ learning motivation increased from 65.98% in Cycle I, categorized as moderate, to 82% in Cycle II, categorized as very high. The implementation of participatory and cooperative learning activities created a more interactive, collaborative, and student-centered learning environment. The novelty of this study lies in its emphasis on motivational and participatory dimensions within Islamic Religious Education through the Talking Stick learning method. This study contributes theoretically to discussions on active and cooperative learning, while practically providing teachers with an alternative instructional strategy to strengthen students’ motivation and classroom engagement.